2021
DOI: 10.25259/sni_820_2021
|View full text |Cite
|
Sign up to set email alerts
|

Hypoplasia of C1’s posterior arch: Is there an ideal anatomical classification?

Abstract: Background: Congenital anomalies of the atlas are rare and usually occur in conjunction with other congenital variants. They include a wide spectrum of anomalies ranging from clefts to hypoplasia or aplasia of its arches that may contribute to spinal cord compressive syndrome. Case Description: A 54-year-old male presented with the sudden onset of a severe quadriparesis and loss of proprioception after a minor fall. The magnetic resonance (MR) scan showed cord compression at the C1 level attributed to C1 a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 9 publications
0
2
0
Order By: Relevance
“…These variations in C1 do not typically affect the stability of the C1 joints and are mostly asymptomatic. However, Pacheco et al (2) propose a new classification of C1 abnormalities, continuing Currarino's classification and highlighting two types. Type A is characterized by hypertrophy of the posterior tubercle, where a fourth ossification center is present, alongside with premature fusion of the lateral sections of the posterior arch.…”
Section: Methodsmentioning
confidence: 99%
“…These variations in C1 do not typically affect the stability of the C1 joints and are mostly asymptomatic. However, Pacheco et al (2) propose a new classification of C1 abnormalities, continuing Currarino's classification and highlighting two types. Type A is characterized by hypertrophy of the posterior tubercle, where a fourth ossification center is present, alongside with premature fusion of the lateral sections of the posterior arch.…”
Section: Methodsmentioning
confidence: 99%
“…Despite its low prevalence, atlas deformity associated with spinal cord compression constitutes a potentially devastating condition, which may lead to quadriplegia and even death (1,2). In 1989, Sawada et al (3) first reported the use of C1 laminectomy (C1L) for a case of canal stenosis at the level of the atlas.…”
Section: Introductionmentioning
confidence: 99%